Dendritic Cells Produce CXCL13 and Participate in the Development of Murine Small Intestine Lymphoid Tissues - McDonald, Keely G. (American Society for Investigative Pathology, 2010)
In the adult intestine, luminal microbiota induce cryptopatches to transform into isolated lymphoid follicles (ILFs), which subsequently act as sites for the generation of IgA responses. The events leading to this conversion are incompletely understood. Dendritic cells (DCs) are components of cryptopatches (CPs) and ILFs and were therefore evaluated in this process. We observed that the adult murine intestine contains clusters of DCs restricted to the CP/ILF continuum. A numerical and cell associative hierarchy in the adult intestine and a chronologic hierarchy in the neonatal intestine demonstrated that these clusters form after the coalescence of CD90(+) cells to form CPs and before the influx of B220(+) B lymphocytes to form ILFs. Cluster formation was dependent on lymphotoxin and the lymphotoxin β receptor and independent of lymphocytes. The ILF DC population was distinguished from that of the lamina propria by the absence of CD4(+)CD11c(+) cells and an increased proportion of CD11c(+)B220(+) cells. The formation of clusters was not limited by DC numbers but was induced by luminal microbiota. Moreover, in the absence of the chemokine CXCL13, CP transformation into ILF was arrested. Furthermore, ILF DCs express CXCL13, and depletion of DCs resulted in regression of ILFs and disorganization of CPs. These results reveal DC participation in ILF transformation and maintenance and suggest that in part this may be due to CXCL13 production by these cells.